Revitalisation of urban infrastructural and industrial facilities for the function of urban agriculture – examples of good practice - Kleszcz Justyna (Lodz University of Technology Press, 2023)
Since the 1960s, people have been looking for new solutions to produce food directly in urban areas. The need of reducing distance between where food is grown and where it is consumed, and to intensify cultivation in order to feed rapidly growing world population, were the main reasons for the concept. This resulted, among others, in the emergence of concept of urban vertical and roof farming but also in a turn towards the historical form of allotment gardens. One of the latest global trends, initiated around 2010, is a shift towards using roof space of existing buildings with different primary functions to introduce integrated rooftop farming as open-air (RTF) or greenhouse (iRTF). Therefore, the aim of the study is to analyse good design practices focused on converting different types of industrial facilities into urban farms of the North American networks Gotham Greens and Lufa Farms. A total of 12 existing buildings were analysed. The study adopted method of literature analysis, case study concluded with comparative analysis of the detailed data collection. The following research has made it possible to identify specific features of buildings which, due to their technical parameters, are predestined to be transformed into multifunctional RTFs. Catalogue of spatial activities that these historical objects undergo in order to be arranged for an atypical both industrial and agricultural function was also compiled.
Keywords: iRTF; multifunctionality; revitalization; urban farming; urban morphology; wielofunkcyjność; rewitalizacja; rolnictwo miejskie; morfologia miast